O discurso midiático acerca da qualidade da educação básica brasileira - Santos, Samuel (2018)
The quality of Brazilian public basic education has been signified as a calamity, either by the media, by surveys (large scale evaluations) or by the pronouncement of social actors (GUSMÃO, 2010). This theme is increasingly recurrent in discourses about education in Brazil. With this scenario in view, the scope of the research is to understanding how the discursive elements in the media field mean the quality of basic public education in Brazil. For the development of this study, we are in the theory and methodology of Discourse Analysis in Brazil (FERREIRA, 2007), with a French background, focusing on studies by Orlandi (1998, 2008, 2009, 2012 and 2014), Althusser (1998), Brandão (2012), Pêcheux (1997, 1999), Courtine (2003, 2014) and other authors who have developed research on discourse and the media and also on quality in education. The corpus of this work is constituted by news, cut from the year 2016, of three sites: Uol, Last second-IG and Unicamp Portal, which highlight the speeches exposed in the media around the issue. Faced with the collected corpus, the following research questions guided the analytical development: a) How does the media address and address this issue of the quality of basic Brazilian education? b) Which ideologies cross the question? c)What cause (s) and solution (s) are (are) pointed out by the media field about this issue? The results obtained from our research point out that the concept of quality, as well as the discourses on education in Brazil, are strongly challenged by the neoliberal capitalist ideology. In this context, we can note that enunciating subjects, education and the term "quality" are constituted from this ideology, in which, what is at stake is education for marketing purposes and, above all, reestablishment of the neoliberal approach, strengthening the discourse on the total quality in education. In addition, large-scale evaluations are signified as determining parameters for measuring quality in education and that the subject teacher implicitly delegates the largest portion of the blame for failure in basic education. The discourses that cross the thematic focus of this research also mean basic education as the support of the educational structure, since it is fundamental for the support of the other educational instances.